Networks and low adoption of hybrid technology: The case of pearl millet in Rajasthan, India - Munasib, Abdul; Roy, Devesh; Birol, Ekin (International Food Policy Research Institute, 2015)
In this paper we study the role of social networks in the context of the low adoption rate of hybrid varieties of pearl millet, an important dry land crop in India. We focus on Rajasthan, which has the lowest adoption rate of hybrid pearl millet varieties among all of the pearl millet-producing states in India. We find evidence of the existence of significant network effects on the adoption of hybrid varieties. However, going a step further, we explain this low rate of adoption in terms of the nature of effective networks for adoption. We find that only close-knit networks, which in light of social fragmentation can limit benefits to only a few farmers, have a significant effect on the adoption of hybrid seeds. The ineffectiveness of farmer groups, mass media, and public extension services—which in principle should be less exclusionary and thus could reach a larger group—can be a contributing factor underlying the low adoption rate of hybrid pearl millet varieties.